2014
DOI: 10.12720/joams.2.1.50-54
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategy Implementation

Abstract: To execute the strategy more effectively, this study proposes an integrated model combining the resourcebased view of 'McKinsey 7S' and the industrial organization point of view. The model was tested through collecting primary data from employees of a disguised transformer manufacturer (TRANSCO). The findings prove that neither the resource-based nor the industrial organization is effective independently towards solving the strategy implementation problem, although the study suggests that the resource-based vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
(24 reference statements)
1
19
1
Order By: Relevance
“…According to [7], the effective implementation of an ordinary strategy can beat the additional rate execution of an exceptional strategy. The scholars further argue that organizations do not fail at the point of developing strategies but at the point of execution of the strategic plans such that they not only spend long hours but also have meager resources in the form of human resources, technical and financial resources.…”
Section: F Policy Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [7], the effective implementation of an ordinary strategy can beat the additional rate execution of an exceptional strategy. The scholars further argue that organizations do not fail at the point of developing strategies but at the point of execution of the strategic plans such that they not only spend long hours but also have meager resources in the form of human resources, technical and financial resources.…”
Section: F Policy Implementationmentioning
confidence: 99%
“…Baroto et al [7] add that adequate allocation of time and its management is a resource allocation issue that could be facilitated by organizational culture. Clan culture (homely working environment), may have diverse and specific influence and varied levels of magnitude of influence on strategy implementation.…”
Section: G Resource Allocationmentioning
confidence: 99%
“…Strategy implementation and strategy formulation of the country administration organizations were related to the strength of participation of local administrative organizations. Baroto et al (2014), conducted a study on effective strategy implementation. The study proposed an integrated model that collected the perspective of resources based on the concept of "McKinsey 7S" and the perspective of industry organizations.…”
Section: Strategy Formulation and The Effectiveness Of Smallsized Schmentioning
confidence: 99%
“…So it can be concluded that strategy is a choice about actions carried out by the organization to achieve its objectives and to achieve excellence competitive. To be more effective in implementing strategies, the approach is unique and that most in accordance with the conditions of internal and external factors and very important challenges (Baroto, Arvand, & Ahmad, 2014).…”
Section: Table 21:-matrix Swot Analysismentioning
confidence: 99%